THE VALUE OF LOCAL APPLICATION OF HYDROGEN PEROXIDE SOLUTION AT THE SITE OF WOUND AFTER MASTECTOMY FOR BREAST CARCINOMA IN REDUCING LOCAL RECURRENCE OF THE TUMOR (Iraqi Journal of Medical Sciences, 2016)
Background: Hydrogen peroxide is produced in normal cells of the body by peroxisomes. Cancer cells have lower respiration rates than normal cells therefore they grow better under low oxygen concentration, and introducing high oxygen levels could retard their growth or kill them. On these bases hydrogen peroxide solution had been applied locally at the site of wound after mastectomy for breast carcinoma to decrease the risk of local recurrence of the tumor.Objective: To evaluate the significance of local application of hydrogen peroxide solution at the site of wound after mastectomy for patients with breast carcinoma in reducing local recurrence of the tumor, and to observe whether it is safe or not.Patients and Methods: One hundred female patients with breast carcinoma and underwent mastectomy in Baghdad hospitals were involved in this study. Patients were divided into two identical groups each with fifty patients. Group 1, patient's wounds were treated locally by hydrogen peroxide solution after mastectomy; whereas the other group (control) did not treat with it. Patients had been followed for survival, recurrence, and complications for 15 years.Results: In group 1; there was no local recurrence, while in the control group, the local recurrence of the tumor was 14% .In group 1,the five, ten, and fifteen years survival were 60%, 14%, and 6% respectively without detectable complications; while in the control group, the 5 year survival was 24%, and no patient survive more than 7 years.Conclusion: Local application of hydrogen peroxide solution at the site of wound after mastectomy for breast carcinoma is safe and may be effective in improving survival rate and reducing local recurrence of the tumor.Key words: Breast carcinoma, local application of hydrogen peroxide solution, local recurrence.